Surface, subsurface and atmosphere exchanges on the satellites of the outer solar system - Tobie, Gabriel; Giese, B.; Hurford, T. A.; Lopes, R. M.; Nimmo, F.; Postberg, Frank; Retherford, K. D.; Schmidt, J.; Spencer, J. R.; Tokano, T.; Turtle, E. P. (Space science reviews, 2010)
The surface morphology of icy moons is affected by several processes implicating exchanges between their subsurfaces and atmospheres (if any). The possible exchange of material between the subsurface and the surface is mainly determined by the mechanical properties of the lithosphere, which isolates the deep, warm and ductile ice material from the cold surface conditions. Exchanges through this layer occur only if it is sufficiently thin and/or if it is fractured owing to tectonic stresses, melt intrusion or impact cratering. If such conditions are met, cryomagma can be released, erupting fresh volatile-rich materials onto the surface. For a very few icy moons (Titan, Triton, Enceladus), the emission of gas associated with cryovolcanic activity is sufficiently large to generate an atmosphere, either long-lived or transient. For those moons, atmosphere-driven processes such as cryovolcanic plume deposition, phase transitions of condensable materials and wind interactions continuously re-shape their surfaces, and are able to transport cryovolcanically generated materials on a global scale. In this chapter, we discuss the physics of these different exchange processes and how they affect the evolution of the satellites’ surfaces.